Prediction of occult lymph node metastasis in squamous cell carcinoma of the oral cavity and the oropharynx using peritumoral Prospero homeobox protein 1 lymphatic nuclear quantification. Issue 9 (4th April 2016) - Mermod, Maxime; Bongiovanni, Massimo; Petrova, Tatiana V.; Dubikovskaya, Elena A.; Simon, Christian; Tolstonog, Genrich; Monnier, Yan
Abstract: Background: The use of lymphatic vessel density as a predictor of occult lymph node metastasis (OLNM) in head and neck squamous cell carcinoma (HNSCC) has never been reported. Methods: Staining of the specific lymphatic endothelial cells nuclear marker, PROX1, as an indicator of lymphatic vessel density was determined by counting the number of positive cells in squamous cell carcinomas (SCCs) of the oral cavity and the oropharynx with clinically negative necks. Correlation with histopathological data was established. Results: Peritumoral PROX1 lymphatic nuclear count significantly correlated with the detection of OLNM in multivariate analysis ( p < .005). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of this parameter was 60%, 95%, 85%, and 90%, respectively. Conclusion: Peritumoral PROX1 lymphatic nuclear count in primary SCCs of the oral cavity and the oropharynx allows accurate prediction of occult lymph node metastasis. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1407–1415, 2016